2018
DOI: 10.1038/s41380-018-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intranasal oxytocin on the core social symptoms of autism spectrum disorder: a randomized clinical trial

Abstract: Although small-scale studies have described the effects of oxytocin on social deficits in autism spectrum disorder (ASD), no large-scale study has been conducted. In this randomized, parallel-group, multicenter, placebo-controlled, double-blind trial in Japan, 106 ASD individuals (18-48 y.o.) were enrolled between Jan 2015 and March 2016. Participants were randomly assigned to a 6-week intranasal oxytocin (48IU/day, n = 53) or placebo (n = 53) group. One-hundred-three participants were analyzed. Since oxytocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
103
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 39 publications
8
103
2
Order By: Relevance
“…The current study provides preliminary evidence that multiple-dose OT treatment may relieve an individual from this increased "need for sameness" and the resulting need for engaging in repetitive and restricted behaviors. Overall, these observed effects on repetitive behaviors are in line with previous trials with adult men with ASD showing beneficial effects of OT on repetitive behaviors after 4 h of intravenous OT administration [4] and after 6 weeks of daily administrations [8,10]. Note however that one 1-week trial with adult men with ASD did not show OT-specific improvements on informant-based reports of repetitive behaviors [9].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The current study provides preliminary evidence that multiple-dose OT treatment may relieve an individual from this increased "need for sameness" and the resulting need for engaging in repetitive and restricted behaviors. Overall, these observed effects on repetitive behaviors are in line with previous trials with adult men with ASD showing beneficial effects of OT on repetitive behaviors after 4 h of intravenous OT administration [4] and after 6 weeks of daily administrations [8,10]. Note however that one 1-week trial with adult men with ASD did not show OT-specific improvements on informant-based reports of repetitive behaviors [9].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Parker et al [14] investigated whether a 4-week intranasal OT treatment could improve core autism characteristics in 32 children (6-12 years old) with ASD and showed an increase in parentreported social responsiveness. Taken together, findings of these initial multiple-dose trials provided indications for a more consistent (positive) pattern of results for OT trials with adults with ASD [8][9][10], compared to trials with children with ASD [11][12][13][14].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…279,280 The physiological roles of these receptors in the actions of oxytocin remain to be clarified. Further studies are also necessary to facilitate therapeutic potentials of oxytocin 281,282 or oxytocin-related treatments including diet ingredients 283…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…To date the functional effects of intranasal OT administration have been based primarily on a single dose and there is evidence that a 24IU dose may be optimal [6]. However, initial clinical trials reporting some therapeutic efficacy have typically used twice-daily treatment protocols lasting a number of weeks [1,[7][8][9][10][11], even though no studies have investigated if this is an optimal strategy. This is an important issue since clinical trials to date have reported relatively modest or inconsistent effects of chronic daily intranasal OT treatment and there is evidence from animal studies for rapid desensitization of OT receptors in some brain regions [12], most notably in the amygdala which mediates many of OTs functional effects on social cognition and anxiety [1].…”
Section: Introductionmentioning
confidence: 99%